A modified azoalbumin technique for the assay of proteolytic enzymes for use in blood group serology. Issue 3 (March 1984) - Phillips, P K; Prior, D; Dawes, B
Abstract : A spectrophotometric assay of proteolytic enzyme activity is described in which the optical density obtained by a given enzyme preparation is related (2 alpha less than 0.01) to the serological activity of that preparation in a two stage technique. The assay appears to be of use for the standardisation of enzyme preparations for use in blood group serology.